Incremental planning of the location of public health facilities in a rural region - Olayinka Waziri Otun (Faculty of Geography, Universitas Gadjah Mada, 2021)
Some people in rural areas are often excluded from using health facilities in developing nations due to political interference in facility location decision-making. Limited attention has been paid in the literature to promoting inclusiveness in public facilities usage in developing nations. Therefore, this study was designed to examine the access to Primary Health Centres (PHCs) in the Yewa region, Nigeria. Data on the 509 settlements and 91 PHCs in the Yewa region were obtained from government directories. The p-median Location-Allocation model was used for data analyses. The study showed that the number of PHCs increased and access to them improved in the Yewa region between 1991 and 2019. It was also shown that inclusiveness in facilities could be promoted by optimally adding new PHCs. The study assessed the effectiveness of past locational decisions, similar to other studies in Bangladesh and India, and revealed that the military administration performed better than the civilian administration in facility location decision-making between 1991 and 2019. The study showed how new facilities could be optimally located to improve access and inclusiveness in public usage.